IMPACT OF ECO-FRIENDLY PROCUREMENT POLICIES ON THE EFFICIENCY OF PUBLIC ENTERPRISES IN RWANDA - Clark , Jason (Ayden International Journal of Banking, Finance and Technology, 2024)
Envy is a universal emotion that can be triggered by upward social comparisons and the possession of prestige products. In this research, we investigate the impact of status hierarchies within brand communities on the occurrence of Malicious and Benign Envy. We conducted two experiments to examine the antecedents and consequences of envy, as well as their effect on members of brand communities. We specifically focused on the role of deservingness and self-brand connection (SBC). In Experiment 1, we found that deservingness affects feelings of both Malicious and Benign Envy. Participants showed Benign Envy toward a higher status target who is deemed worthy of good fortune, but experienced Malicious Envy if the higher status member of the brand community was deemed unworthy of the good fortune. In Experiment 2, we manipulated deservingness and SBC to investigate their effects on the emotional presence of Malicious and Benign Envy. We found that for Malicious Envy, the impact of the source of the material item was greater for high SBC participants than for low SBC participants. Our research sheds light on the impact of status hierarchies within brand communities on Envy and provides insights into the role of deservingness and SBC in this process. The findings suggest that luxury brands can create hierarchical groups within their communities, leading to upward social comparisons and potential envy. We discuss the practical implications of our findings for marketers and brand managers, as well as future research directions.